2010
DOI: 10.1021/bm100540t
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer to Millimeter Scale Peptide-Porphyrin Materials

Abstract: AQ-Pal14 is a 30-residue polypeptide that was designed to form an α-helical coiled coil which contains a metal-binding 4-pyridylalanine residue on its solvent-exposed surface. However, characterization of this peptide shows that it exists as a three-stranded coiled coil, and not a twostranded one as predicted from its design. Reaction with cobalt(III) protoporphyrin IX (Co-PPIX) produces a six-coordinate Co-PPIX(AQ-Pal14) 2 species which creates two coiled-coil oligomerization domains coordinated to opposite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…It is usually expected that the respective placement of isoleucine and leucine residues at the first and the fourth heptad positions of a coiled coil sequence promotes the formation of two-stranded coiled coils [56]. However, recent studies on the closely related AQ-Pal14 [47] and CC-pIL [57] peptides showed that they both unexpectedly formed a three-stranded coiled coil, making us anticipate the analogous behavior of the AQ-C16C19 peptide.…”
Section: Design Of the Coiled Coilmentioning
confidence: 91%
See 2 more Smart Citations
“…It is usually expected that the respective placement of isoleucine and leucine residues at the first and the fourth heptad positions of a coiled coil sequence promotes the formation of two-stranded coiled coils [56]. However, recent studies on the closely related AQ-Pal14 [47] and CC-pIL [57] peptides showed that they both unexpectedly formed a three-stranded coiled coil, making us anticipate the analogous behavior of the AQ-C16C19 peptide.…”
Section: Design Of the Coiled Coilmentioning
confidence: 91%
“…Buffers contained 0-1000 mM KCl to maintain the desired ionic strength. The instrumentation setup employed for the analysis of eluates is described earlier [47]. The dn/dc value for the metal-free AQ-C16C19 in the phosphate buffer at pH 7 was obtained in the batch analysis of a series of dilutions of the peptide using the Optilab rEX instrument.…”
Section: Size-exclusion Chromatography With Static Light-scattering Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In nature, elegant arrangements of peptide–porphyrin conjugates are essential in conducting biological processes . This has inspired researchers worldwide to investigate the self‐assembly and supramolecular structures of porphyrin–peptide conjugates mimicking the structure and role of natural porphyrin . In this work, we explore the development and use of l ‐ and d ‐phenylalanine‐substituted protoporphyrin IX derivatives 1 and 2 , respectively, for the solvophobic‐controlled assembly of nanostructures (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[24] They showed that a polypeptide bearing 4pyridylalanine self-assembles into globular and rod-like morphologies through metal-binding interactions with Co-PP-IX (13) (Figure 2). [24] They showed that a polypeptide bearing 4pyridylalanine self-assembles into globular and rod-like morphologies through metal-binding interactions with Co-PP-IX (13) (Figure 2).…”
Section: Mixed Assembliesmentioning
confidence: 99%